Visual effects in a digital world - Goulekas, Karen E. (San Francisco, CA : Morgan Kaufmann, 2001)
As the visual effects industry has diversified, so too have the books written to serve the needs of this industry. Today there are hundreds of highly specialized titles focusing on particular aspects of film and broadcast animation, computer graphics, stage photography, miniature photography, color theory, and many others. Visual Effects in a Digital World offers a much-needed reconsolidation of this knowledge. All of the industry's workers frequently need to understand concepts from other specialties, and this book-the only one of its kind-lets them look up and grasp the basics of any visual effects concept in a matter of seconds. It's a great way for everyone, regardless of experience, to find their way through the jargon and learn what they need to know. * Authoritative coverage from a winner visual effects expert-winner of a British Academy Award and two Emmys. * Cover topics such as computer graphics, digital compositing, live action, stage, and miniature photography, and a wide range of computer and Internet concepts. * Offers job descriptions for positions found throughout the industry. * Demystifies the jargon used by practitioners in every subspecialty.
As this title is a glossary, no table of contents is included.
Includes bibliographical references (p. 593-600).
Keywords: Image processing -- Digital techniques -- Dictionaries; Electronic books; Dictionaries